Design of a 75 H.P. A.S.M.E. standard multitubular boiler - Richards, H. P. (My University, 1902)
Introduction: Design for a 75 H. P. (A. S. M. E. standard) horizontal multitubular boiler. Working pressure if 100 pounds per sq. inch. Test pressure is 150 pounds per sq. inch. Length of tubes, 15 feet which is not to exceed 60 diameter the heating surface to be about 37 times the grate surface; the steam space about one-half the water space; and the tube area between one-seventh and one-eighth the grate area. The boiler is to be supplied with two steam outlets for five inch pipes, a hand hole four by six inches (4” x 6”) at the bottom of each tube sheet, and a man hold eleven by fifteen inches (11” x 15”) inside. Provisions are also to be made for the attachment of a one and one-fourth (1-1/4”) inch feed pipe and a two (2”) inch blow off pipe. The reach of the riveting machine is sex feet, six inches (6’ – 6”).
Citation: Richards, H. P. Design of a 75 H.P. A.S.M.E. standard multitubular boiler. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Boiler; Design; Diagrams; Engineering Plans; Mechanical Engineering; Theses